ACCESS TO TECHNOLOGY AND THE TRANSFER FUNCTION OF COMMUNITY COLLEGES: EVIDENCE FROM A FIELD EXPERIMENT. - FAIRLIE, ROBERT W.; GRUNBERG, SAMANTHA H. (Economic Inquiry, 2014)
Access to information may represent an important barrier to learning about and ultimately transferring to 4-year colleges for low-income community college students. This article explores the role that access to information technology, in particular, plays in enhancing, or possibly detracting from, the transfer function of the community college. Using data from the first-ever field experiment randomly providing free computers to students, we examine the relationships between access to home computers and enrollment in transferable courses and actual transfers to 4-year colleges. The results from the field experiment indicate that the treatment group of students receiving free computers has a 4.5 percentage point higher probability of taking transferable courses than the control group of students not receiving free computers. The evidence is less clear for the effects on actual transfers to 4-year colleges and the probability of using a computer to search for college information (which possibly represents one of the mechanisms for positive effects). In both cases, point estimates are positive, but the confidence intervals are wide. Finally, power calculations indicate that sample sizes would have to be considerably larger to find statistically significant treatment effects and reasonably precise confidence intervals given the actual transfer rate point estimates. (JEL J24, O33, I23, I24)